2010
DOI: 10.3844/ajavsp.2010.282.288
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Citric Acid and Microbial Phytase on Growth Performance and Carcass Characteristics of Broiler Chickens

Abstract: Problem statement:The aim of this study was to investigated the effects of adding citric acid and microbial phytase supplementation (Natuphos ® ) on growth performance and carcass characteristics of broiler chickens fed corn soybean meal base diets. Approach: The experiment included nine treatments with 10 birds in each replicate using a 3×3 factorial design for two main factors of citric acid (0, 3 and 6%) and three phytase enzyme (0, 500 and 1000 IU kg ). The diets were formulated based upon corn-soybean mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
3
11
1
Order By: Relevance
“…If applied correctly, organic acids function in poultry, not only as a growth promoter but also as a meaningful mechanism for controlling both pathogenic and non-pathogenic bacteria (Wolfenden et al, 2007). Moreover, feeding organic acids are believed to have several beneficial effects such as improving feed conversion ratio, growth performance, enhancing mineral absorption and speeding recovery from fatigue (Zeinb, 2004;Nourmohammadi et al, 2010b). The antibacterial activity of organic acids is related to reduction of pH, as well as their ability to dissociate that is determined by the pKa-value of the respective acid and pH of the surrounding environment, because the antibacterial activity increases with decreasing pH value.…”
Section: Discussionmentioning
confidence: 99%
“…If applied correctly, organic acids function in poultry, not only as a growth promoter but also as a meaningful mechanism for controlling both pathogenic and non-pathogenic bacteria (Wolfenden et al, 2007). Moreover, feeding organic acids are believed to have several beneficial effects such as improving feed conversion ratio, growth performance, enhancing mineral absorption and speeding recovery from fatigue (Zeinb, 2004;Nourmohammadi et al, 2010b). The antibacterial activity of organic acids is related to reduction of pH, as well as their ability to dissociate that is determined by the pKa-value of the respective acid and pH of the surrounding environment, because the antibacterial activity increases with decreasing pH value.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies were inconsistent; Wickramasinghe et al (2014) reported that 2% dietary CA had no significant effect on the pancreas, gizzard and liver weights and ratios. Similarly, Nourmohammadi et al (2010) showed that supplementation of 3 or 6% CA to broiler diet did not significantly affect liver weight. However, the relative weight of proventriculus and gizzard increased significantly by 6% CA.…”
Section: Digestive Tract Parameters and Immune Organsmentioning
confidence: 95%
“…The authors attributed the reduction in the feed intake to the strong taste associated with the organic acids which would have decreased the palatability of the feed, thereby reducing feed intake. Also, Nourmohammadi et al (2010) reported positive effects from the utilization of 3% CA in broiler diets. They concluded that CA provided suitable pH in the gut for proteolytic enzymes activity and increased feed digestion by a reduction in the gut microflora.…”
Section: Table (1 B) Formulation and Chemical Analysis (Calculated mentioning
confidence: 96%
See 1 more Smart Citation
“…D or Ca of chickens fed a diet containing 0, 0.25, 0.75 and 1.25% CA (Islam et al, 2010). In addition, CA affected mineral utilization, but did not affect the plasma mineral contents (Nourmohammadi et al, 2010). These differences in the response to CA may be due to strain differences, dietary composition, hygienic conditions and the hormonal balance responsible for maintaining Ca and P homeostasis (Fraser, 1988).…”
Section: Hemato-biochemical Parametersmentioning
confidence: 99%